Orthodontic approach in the presence of mesiodens: a case report - Azuara Santana, Daniela Paola (2020)
Mesiodens are supernumerary teeth located between the two upper central incisors whose presence could contribute to the development of malocclusions. This report presents the case of an 8-year-old male patient, who had a mesiodens and an additional supernumerary tooth close to the midline, who were deviating the eruptive path of the permanent incisors, as well as causing severe axial rotation. The supernumerary teeth were extracted and two years later in the absence of spontaneous correction in the position of the affected teeth, the corrective treatment took process using 4x2 orthodontic appliances. Subsequently, when the permanent dentition was complete, full orthodontic appliances were installed, achieving satisfactory results at the end of the treatment. The timely extraction of the supernumerary teeth allowed, although with the presence of malpositions, the complete eruption of the central incisors, reducing the severity of the clinical condition and, consequently, the complexity of orthodontic treatment. Next, we present a treatment proposal to guide the orthodontist in the decision-making in the presence of mesiodens.